Comparative Genome Analysis of the Genus Thiothrix Involving Three Novel Species, Thiothrix subterranea sp. nov. Ku-5, Thiothrix litoralis sp. nov. AS and “Candidatus Thiothrix anitrata” sp. nov. A52, Revealed the Conservation of the Pathways of Dissimilatory Sulfur Metabolism and Variations in the Genetic Inventory for Nitrogen Metabolism and Autotrophic Carbon Fixation - Ravin, Nikolai V.; Rudenko, Tatyana S.; Smolyakov, Dmitry D.; Beletsky, Alexey V.; Rakitin, Andrey L.; Markov, Nikita D.; Fomenkov, Alexey; Sun, Luo; Roberts, Richard J.; Novikov, Andrey A.; Karnachuk, Olga V.; Grabovich, Margarita Y. (Frontiers in Microbiology, 2021)
Two strains of filamentous, colorless sulfur bacteria were isolated from bacterial fouling in the outflow of hydrogen sulfide-containing waters from a coal mine (Thiothrix sp. Ku-5) and on the seashore of the White Sea (Thiothrix sp. AS). Metagenome-assembled genome (MAG) A52 was obtained from a sulfidic spring in the Volgograd region, Russia. Phylogenetic analysis based on the 16S rRNA gene sequences showed that all genomes represented the genus Thiothrix. Based on their average nucleotide identity and digital DNA-DNA hybridization data these new isolates and the MAG represent three species within the genus Thiothrix with the proposed names Thiothrix subterranea sp. nov. Ku-5T, Thiothrix litoralis sp. nov. AST, and ‘Candidatus Thiothrix anitrata’ sp. nov. A52. The complete genome sequences of Thiothrix fructosivorans QT and Thiothrix unzii A1T were determined. Complete genomes of seven Thiothrix isolates, as well as three MAGs, were used for pangenome analysis. The Thiothrix core genome consisted of 1,355 genes, including ones for the glycolysis, the tricarboxylic acid cycle, the aerobic respiratory chain, and the Calvin cycle of carbon fixation. Genes for dissimilatory oxidation of reduced sulfur compounds, namely the branched SOX system (SoxAXBYZ), direct (soeABC) and indirect (aprAB, sat) pathways of sulfite oxidation, sulfur oxidation complex Dsr (dsrABEFHСEMKLJONR), sulfide oxidation systems SQR (sqrA, sqrF) and FCSD (fccAB) were found in the core genome. Genomes differ in the set of genes for dissimilatory reduction of nitrogen compounds, nitrogen fixation, and the presence of various types of RubisCO.